Enzyme-inspired metal-organic framework materials for supramolecular catalysis - Samarakoon, Kanchana Prabodhani (Kansas State University, 2022)
This thesis describes to methods for generating multifunctional, enzyme-inspired metal-organic frameworks (MOF) catalysts: 1. Synthesis of a modifiable homochiral MOF material by incorporating a well-known solution phase catalyst 2. Use of a uniform post-synthetic modification strategy to introduce different chemical functionalities, one being a catalytic group. In Chapter 2, using an established mixed-linker pillared MOF synthesis strategy, we incorporated a solution phase catalyst BINAPO (2,2′-bis(diphenylphosphoryl)-1,1′-binaphthyl) and a modifiable ligand, BDC-NH₂ (2-amino-1,4-benzenedicarboxalic acid) into a modifiable homochiral MOF. We successfully modified the free -NH₂ groups of the modifiable MOF with cyclic anhydrides proving our material is modifiable. We then used both materials as the catalysts for the cyanosilylation of benzaldehyde. Our materials exhibited modest catalytic activity but our efforts at synthesizing a modifiable homochiral material were successful. For the second method, we introduced two proofs of concept with respect to the generation of uniformly multifunctionalized MOF pores. In Chapter 3 we demonstrated the uniform covalent bifunctionalization of a well-defined MOF, KSU-1, to achieve uniformly multifunctionalized confined spaces, which was the first example of uniform covalent functionalization of a MOF. In Chapter 4, we extended our work to orthogonal functionalization which allowed us to generate a uniformly multifunctionalized MOF, not only through multiple paths, but also in a simultaneous one-pot reaction. Finally, in Chapter 5 we used the methods we developed in Chapter 3 and 4 to construct enzyme inspired chiral Brønsted acid MOF catalysts to use in asymmetric epoxide ring opening. Using our unique strategy of uniform independent bifunctionalization, we successful installed a Brønsted acid catalyst and a chiral group into a well-defined MOF, KSU-1, to obtain our desired catalyst.
Keywords: Metal-organic frameworks; MOFs; Supramolecular chemistry; Supramolecular catalysis; Enzyme-inspired